Inclusive Practice in South Africa: A Deaf Education Perspective - Peel, Emma Louise (My University, 2006)
In accordance with Education policy post 1994 there is currently a move in South Africa toward implementing an inclusive approach to educating learners who experience barriers to learning into regular/mainstream schools. Such an inclusive philosophy is considered, at policy level, to be the most effective means of combating discriminatory attitudes, creating welcoming communities, building an inclusive society and achieving education for all (Department of Education, 2001). From an inclusive viewpoint, it is important that all learners are given the best education possible from an academic, emotional and social perspective and emphasis is placed on, educating the whole child by meeting individual needs through the identification and accommodation of any barriers to learning. Within such an education and training system, it is important that Deaf learners are not excluded and that the practice of inclusion takes into account the needs of all Deaf learners. The intention of this research project is to provide an accurate account of the current situations in schools for the Deaf throughout South Africa with regards to barriers to learning and development. It will examine whether these schools, currently, foster the ideals of inclusion as made explicit in White Paper Six (Department of Education, 2001). This thesis will also investigate whether Deaf learners in schools for the Deaf, have access to the most appropriate, least restrictive barrier free education. In order to achieve this, a questionnaire, based on the barriers to learning and development as identified by the above-mentioned document, was sent by post to every principal working in schools for the Deaf in South Africa. In addition, the research intends to determine whether barriers to learning and development are presently being experienced by Deaf learners in current schools for the Deaf and if so, what barriers are being experienced and how these barriers can be addressed and prevented so that Deaf learners be accommodated in a manner that promotes a school environment that is most appropriate and least restrictive for Deaf learners. From the findings it was revealed that schools for the Deaf do not foster inclusive principles as many Deaf learners experience barriers to learning and development as identified in White Paper 6 (Department of Education, 2001: 7 & 18) within schools for the Deaf. To address the barriers found in the findings of the study, this dissertation provides recommendations to assist principals with strategies and information necessary for transforming schools for the Deaf in order to become inclusive and thus provide Deaf learners with access to the most appropriate, least restrictive education possible.
Master of Education - Deaf Studies
Keywords: deaf; south africa; deaf education; Deaf Community; DEAFSA; UNESCO